RESEÑA: INTRODUCCIÓN A LA INVESTIGACIÓN CUALITATIVA. UWE FLICK. - DIEGO FABIAN VIZCAINO AREVALO; OLGA LUCIA CASTIBLANCO ABRIL (Universidad Distrital Francisco José de Caldas, 2010)
This review content, basic data of the author, revised editions of the book, and interpretation through graphical representations with the main message that the author wants to convey in the work. In general is a book for both novice researchers, and for experienced researchers, because it gives a detailed description of qualitative research and also offers features to deepen the subject.